Brain MRI features of anti-N-methyl-D-aspartate (anti-NMDA) receptor encephalitis secondary to central nervous system infection in adult patients. (February 2023) - Piao, Sirong; Bao, Yifang; Yang, Liqin; Zhang, Yi; Hu, Bin; Li, Haiqing; Geng, Daoying; Li, Yuxin
Background: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis secondary to central nervous system (CNS) infection is a unique subtype of the autoimmune-mediated disease, of which the imaging features are unclear. Purpose: To compare the brain magnetic resonance imaging (MRI) features between the anti-NMDAR encephalitis secondary to CNS infection and that without initial infection. Material and Methods: A total of 70 adult patients with anti-NMDAR encephalitis were retrospectively enrolled (24 in the post-infection group, 46 in the non-infection-related group). Their clinical and imaging features (lesion distribution, lesion shape, enhancement pattern, brain atrophy) were reviewed and summarized. Lesion distributions were compared between the two groups on lesion probability maps. Results: The patients with normal brain MRI scans in the post-infection group were less than those in the non-infection related group (29% vs. 63%; P  = 0.0113). Among the 24 patients in the post-infection group, visible lesions were shown at the anti-NMDAR encephalitis onset in 17 patients; lesion distribution was more diffuse than the non-infection-related group, showing higher lesion peak probabilities in the bilateral hippocampus, frontal lobe, temporal lobe, insula, and cingulate. The lesions with contrast enhancement were also more common in the post-infection group than the non-infection-related group (7/13 vs. 2/10). Brain atrophy was observed in eight patients in the post-infection group and three in the non-infection-related group. Conclusion: Anti-NMDAR encephalitis secondary to CNS infection has its imaging features—extensive lesion distribution, leptomeningeal enhancement, early atrophy, and necrosis—that could deepen the understanding of the pathophysiology and manifestation of the autoimmune encephalitis besides the classic type.